Association of Cardiovascular Risk Factors With Major and Minor Electrocardiographic Abnormalities: A Report From the Cross‐Sectional Phase of Tehran Cohort Study - Pooria Ahmadi; Sajjad Ahmadi‐Renani; Parmida Sadat Pezeshki; Sepehr Nayebirad; Arash Jalali; Akbar Shafiee; Aryan Ayati; Arian Afzalian; Farshid Alaeddini; Soheil Saadat; Farzad Masoudkabir; Ali Vasheghani‐Farahani; et al. (Health Science Reports)
ABSTRACT Background and Aims In the current study, we aimed to identify the association between major and minor electrocardiographic abnormalities and cardiovascular risk factors. Methods We used the Tehran cohort study baseline data, an ongoing multidisciplinary, longitudinal study designed to identify cardiovascular disease risk factors in the adult population of Tehran. The electrocardiograms (ECGs) of 7630 Iranian adults aged 35 years and above were analyzed. ECG abnormalities were categorized into major or minor groups based on their clinical importance. Results were obtained by multivariable logistic regression and are expressed as odds ratios (ORs). Results A total of 756 (9.9%) participants had major ECG abnormalities, while minor abnormalities were detected in 2526 (33.1%). Males comprised 45.8% of the total population, and 41.8% of them had minor abnormalities. Individuals with older age, diabetes (OR = 1.35; 95% CI: 1.11–1.64), and hypertension (OR = 2.21; 95% CI: 1.82–2.68) had an increased risk of major ECG abnormalities. In contrast, intermediate (OR = 0.69; 95% CI: 0.57–0.84) and high physical activity levels (OR = 0.66; 95% CI: 0.51–0.86) were associated with a lower prevalence of major abnormalities. Male sex, older age, hypertension, and current smoking were also associated with an increased prevalence of ECG abnormalities combined (major or minor). Conclusion Major and minor ECG abnormalities are linked with important cardiovascular risk factors such as diabetes and hypertension. Since these abnormalities have been associated with poor outcomes, screening patients with cardiovascular risk factors with an ECG may distinguish high‐risk individuals who require appropriate care and follow‐up.